Recent advances in liver imaging. (October 2010) - Mutter, D; Soler, L; Marescaux, J
Liver surgery remains a difficult challenge in which preoperative data analysis and strategy definition may play a significant role in the success of the procedure. Medical image processing led to a major improvement of patient care by guiding the surgical gesture. From this initial data, new technologies of virtual reality and augmented reality can increase the potential of such images. The 3D modeling of the liver of patients from their CT scan or MRI thus allows an improved surgical planning. Simulation allows the procedure to be simulated preoperatively and offers the opportunity to train the surgical gesture before carrying it out. These three preoperative steps can be used intraoperatively thanks to the development of augmented reality, which consists of superimposing the preoperative 3D modeling of the patient onto the real intraoperative view of the patient and his/her organs. Augmented reality provides surgeons with a transparent view of the patient. This facilitated the intraoperative identification of the vascular anatomy and the control of the segmental arteries and veins in liver surgery, thus preventing intraoperative bleeding. It can also offer guidance due to the virtual improvement of their real surgical tools, which are tracked in real-time during the procedure. During the surgical procedure, augmented reality, therefore, offers surgeons a transparent view of their patient, which will lead to the automation of the most complex maneuvers. The new ways of processing and analyzing liver images have dramatically changed the approach to liver surgery.